2018
DOI: 10.21873/anticanres.13112
|View full text |Cite
|
Sign up to set email alerts
|

Positive Association of Male Overactive Bladder Symptoms and Androgen Deprivation: A Nationwide Population-based Cohort Study

Abstract: Background/Aim: The role of androgen in the modulation of voiding function is still uncertain. The aim of this study was to evaluate the association of androgen deprivation therapy (ADT) and overactive bladder (OAB) in men in a population-based cohort. Materials and Methods: This study examined the records of newly-diagnosed prostate cancer subjects receiving ADT only in the Taiwan National Health Insurance Research Database in the years between 2001 and 2007.As controls men without cancer were selected and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…The higher serum levels of testosterone generated by testosterone supplementation were associated with reduced IPSS, probably indicating a correlation between serum testosterone level and their effects on LUTS 21 . Especially, lower IPSS-ss were reported in patients with testosterone supplementation than control by a more recent study based on a large registry data 22 , 23 . In the same context, an Asian study that investigated the relationship between male overactive bladder (OAB) symptoms and androgen deprivation revealed that ADT in patients with PCa was associated with an increased risk of OAB that was ADT duration-dependent 23 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The higher serum levels of testosterone generated by testosterone supplementation were associated with reduced IPSS, probably indicating a correlation between serum testosterone level and their effects on LUTS 21 . Especially, lower IPSS-ss were reported in patients with testosterone supplementation than control by a more recent study based on a large registry data 22 , 23 . In the same context, an Asian study that investigated the relationship between male overactive bladder (OAB) symptoms and androgen deprivation revealed that ADT in patients with PCa was associated with an increased risk of OAB that was ADT duration-dependent 23 .…”
Section: Discussionmentioning
confidence: 92%
“…Especially, lower IPSS-ss were reported in patients with testosterone supplementation than control by a more recent study based on a large registry data 22 , 23 . In the same context, an Asian study that investigated the relationship between male overactive bladder (OAB) symptoms and androgen deprivation revealed that ADT in patients with PCa was associated with an increased risk of OAB that was ADT duration-dependent 23 . Taken together, considering that the changes in both PV and testosterone during ADT can affect LUTS, analyzing that the combined effect of the two may provide relevant suggestions to enlighten the actual cause of changes in LUTS in patients with PCa undergoing ADT.…”
Section: Discussionmentioning
confidence: 92%
“…Especially, lower IPSS-ss were reported in patients with testosterone supplementation than control by a more recent study based on a large registry data [2122]. In the same context, an Asian study that investigated the relationship between male overactive bladder (OAB) symptoms and androgen deprivation revealed that ADT in patients with PCa was associated with an increased risk of OAB that was ADT duration-dependent [22]. Taken together, considering that the changes in both PV and testosterone during ADT can affect LUTS, analyzing that the combined effect of the two may provide relevant suggestions to enlighten the actual cause of changes in LUTS in patients with PCa undergoing ADT.…”
Section: Discussionmentioning
confidence: 99%
“…Unusually strong longitudinal cohort studies of incontinence were presented. Using a sample of 16 128 women in the Taiwanese National Health Insurance Research Database, small but statistically significant excess risks of LUTS were shown after a breast cancer diagnosis, most likely associated with oestrogen deprivation therapy (Abstract 208). Using a sample of 2115 women enrolled in the French GAZEL cohort, between 2000 and 2008, a positive benefit of incontinence surgery for severe stress incontinence was observed, but offset against an increased risk of mixed or urgency incontinence, consistent with our understanding of the risks of midurethral sling surgery (Abstract 209).…”
Section: Epidemiologymentioning
confidence: 99%